Production of Hybrid Basmati Rice in Kenya: Progress and Challenges - Njiruh, Nthakanio P.; Kanya, James I.; Kimani, John M.; Wajogu, Raphael (My University, 2013)
Photoperiod sensitive genic male sterile (PGMS) and Thermosensitive genic male sterile (TGMS) rice varieties require a long day light length and high temperature respectively growth conditions for them to be completely male sterile. In hybrid rice seed technology complete male sterility is required in pollen recipient parent so as to avoid contamination of hybrid seeds by selfbred seeds. Natural weather conditions necessary to achieve this are difficulty to obtain in the tropics thus limiting the use of the PGMS/TGMS lines. In this research PGMS and TGMS rice plants were grown under a tropical daylight length that was prolonged to 14hour using solar light illumination gadget while minimum daytime temperature was raised to ≥36°C using greenhouse. This was done under non-automated ordinary greenhouse conditions. The objective was to induce complete male sterility in PGMS or TGMS and to produce hybrid seeds. Under greenhouse growth conditions it was possible to induce complete male sterility in PGMS and TGMS. When grown outside the greenhouse the PGMS and TGMS were male fertile which is required for their own self propagation. The male sterile plants were cross pollinated with elite basmati rice to obtained F1 seeds. This paves the way for hybrid rice production in Kenya. One other major challenge is that the characteristic aroma found in basmati is not felt in hybrid plants because it is under a recessive gene control.
Keywords: Basmati; heterosis; hybrid; PGMS; TGMS